Moderating Effect of Board Characteristics on the Association between Asset Liability Management and Financial Performance of Commercial Banks in Nigeria - AKINSELURE, Oluwafemi Philip; AYOOLA, Tajudeen John; AREGBESOLA, Olateju Dolapo (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024, 2024)
Asset liability management and consistent improvement in financial performance are the responsibility of the Board of Directors of commercial banks, yet studies on the impact of asset liability management on the financial performance of commercial banks in Sub-Saharan Africa have excluded board characteristics variable from their statistical model. This study examines the moderating effect of board characteristics and asset liability management on the financial performance of commercial banks in Nigeria. Commercial banks. It was based on secondary data, obtained from annual reports of commercial banks in Nigeria, the study covered the period starting from 2012 to 2021 and it purposively selected eleven (11) commercial banks out of fourteen (14) commercial banks in Nigeria. The statistical analysis was done using LASSO (Least Absolute Shrinkage Selection Operator). The findings of the study revealed that the moderating effect of board characteristics and asset liability management had a statistically significant impact on the financial performance of commercial banks in Nigeria because the p-values (0.04;0.03,0.02,0.01, and 0.005) obtained using LASSO were less than the 5% statistical threshold used in this study. The study concluded that the board of directors of commercial banks in Nigeria should ensure that they appoint board members who have expertise and experience in the establishment of asset liability management since its interaction with board characteristics showed a statistically significant impact on the financial performance of the bank.